2021
DOI: 10.1016/j.heliyon.2021.e05929
|View full text |Cite
|
Sign up to set email alerts
|

Roman Catholicism and fertility among the Mbaise, Southeast, Nigeria

Abstract: There is a prevalence of high fertility among the Mbaise of Imo State, Nigeria. This is linked to the perceptions, beliefs and practices of the people. The voluntaristic social action theory by Talcott Parsons and Proximate determinants of fertility framework by Bongaarts were utilized to highlight the links between Catholicism and fertility, as well as socio-cultural variables and fertility behaviour by showing strength of their separate and combined relationships. Data were gathered through survey questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Further, injunctive norms highlighted in our study reveal that religious leaders and messages from religious institutions in uence decision-making and perceptions about contraceptive use and family size. This nding aligns with other studies that concluded that there is a relationship between religious condemnation of contraceptives and underutilization of family planning services [22,23].…”
Section: Beliefs About Birth Interval and Family Sizes That Others Ap...supporting
confidence: 90%
“…Further, injunctive norms highlighted in our study reveal that religious leaders and messages from religious institutions in uence decision-making and perceptions about contraceptive use and family size. This nding aligns with other studies that concluded that there is a relationship between religious condemnation of contraceptives and underutilization of family planning services [22,23].…”
Section: Beliefs About Birth Interval and Family Sizes That Others Ap...supporting
confidence: 90%
“…A very common finding (n = 90) is a negative relationship between formal schooling and desired fertility. Two studies found that higher education was associated with high fertility [ 140 , 141 ]. In these cases, the authors may be detecting short-term differentials: more schooling brings access to better jobs and increased income, producing a temporary increase in desired fertility, followed by a transitional period and a leveling out or decrease in the desire for more children.…”
Section: Resultsmentioning
confidence: 99%